Muscle performance using MC-sensor during FES-evoked contractions in individuals with spinal cord injury / Nor Zainah Mohamad - Nor Zainah , Mohamad (2019)
Muscle contractions induced by functional electrical stimulation (FES) can contribute in rapid muscle fatigue. Muscle fatigue is one of the main limiting factors in FES. Spinal Cord Injury (SCI) patients experience fatigue in muscle early in prolonged FES-evoked activities than normal person. Due to the absence or compromised proprioceptive response that characterizes paralyzed muscle activities, it is crucial to monitor muscular forces generated during FES-evoked activity. An MMG-based muscle contraction (MC) sensor is presented in this research in which it was attached to the skin surface, used to monitor paralyzed muscle tension throughout a fatiguing functional electrical stimulation evoked contraction. As the MC sensor tip exerts compression pressure, which causes a dent on the skin and the intermediate layer above the muscle and also the muscle itself, the force measured by the sensor tip is proportional to muscle tension. Nine individuals with complete spinal lesion volunteered to participate in two separate trials, one to investigate MC-torque correlation while the other to investigate fatigue. The quadriceps muscle contraction under isometric conditions on Biodex Dynamometer was induced by electrical current in randomized order using Rehastim stimulator for the SCI participants, while measurements with MC sensor was recorded. Among SCI, MC-sensor-predicted measures of dynamometer torques, including the signal peak (SP) and signal average (SA), were highly associated with isometric knee extension peak torque (SP: r = 0.91, p< 0.0001), and average torque (SA: r = 0.89, p< 0.0001), respectively. Bland-Altman (BA) analyses with Lin’s concordance (ρC) revealed good association between MC-sensor-of isokinetic speeds, while the relationship between signal average of dyna-torque and MC-voltage were highly correlated (R2=85%). These findings demonstrated that a skin-surface muscle mechanomyography sensor was an accurate proxy for electrically-evoked muscle contraction torque when directly measured during isometric dynamometry in individuals with SCI. This study demonstrates the novel application of MC sensor in FES-evoked contraction application with individuals with SCI, which may be the highly sought-after solution for contraction feedback directly at the muscle level.